Situation Report: Poland, 30 October 1967 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Gomulka on Germany, China Nina Karsow [Karsov] Sentenced to Three Years Imprisonment Church-State Relations Lawyers' Congress Polish-Austrian Trade Agreement Poland, Ghana Sign Trade Protocol